Case Study of Solid Waste Based Soft Soil Solidifying Materials Applied in Deep Mixing Pile - Benan Shu; Haoliang Gong; Shaoming Chen; Yanfei Ren; Yongling Li; Tengyu Yang; Guodong Zeng; Min Zhou; Diego Maria Barbieri; Yuanyuan Li (Buildings, 2022)
The research on solid waste based soft soil solidifying materials has received extensive attention in recent years. However, the properties of deep mixing piles are significantly affected by the construction technology. In view of this, this work carried out the systematic study on the influence of materials, the mixing tool and process optimization on the integrity and mechanical properties of deep mixing piles. Factors considered include the shape of the blade (strip and meniscus), the types of solidifying materials (PO 42.5 cement, self-developed soft soil solidifying agent), the content (50 kg/m, 65 kg/m, 80 kg/m and 100 kg/m) and how many times the materials needed to be mixed (two, four and six times). The solidification mechanism was analyzed. The results showed that the utilization of a meniscus blade contributed to the excellent integrity of the deep mixing pile, as well as solved the problems of oozing slurry and wrapped blade during construction. Mixing the materials four times is the most suitable for the construction of deep mixing piles in organic clay. The solidifying agent deep mixing pile showed satisfactory early and late strength. Microscopic analysis showed that more calcium silicate hydrate and ettringite formed in the solidifying agent solidified soil. Organic clay particles were better cemented and pores were fully filled, so that the solidified soil showed an integral and dense structure. The microscopically integral and dense structure contributed to the excellent integrity and mechanical properties of the solidifying agent deep mixing pile.